Controversies over Infective Endocarditis Prophylaxis and the need for National Guidelines - Selim Ahmed; Liew, Constance Sat Lin; Doreen Sumpat; Alvin Oliver Payus; Lo, Zhen Zhen; Mandrinos Symeon; Kew, Teik Seih; Rajesh Kumar Muniandy; Raman S RM Subramaniam Chettiar (EManuscript Services, 2022)
Infective endocarditis (IE) is a relatively rare but invariably fatal disease if left untreated. Over decades, individuals with certain congenital or acquired heart defects were given antibiotic prophylaxis before certain procedures to prevent IE. However, controversies on this regimen have begun to grow since 2002 and in 2007-2008, three major international health organizations, the American Heart Association (AHA), the European Society for Cardiology (ESC), and the National Institute for Health and Clinical Excellence (NICE), UK published have their revised guidelines where AHA and ESC markedly shortened the list of indications for IE prophylaxis and NICE abandoned the concept of IE prophylaxis altogether. This has literally divided not only the medical practitioners around the world but practitioners within countries who used to follow either AHA, ESC or NHS guidelines in absence of their own national guidelines. This chaotic situation has also affected the medical teaching in those countries because of contradictory teaching from teachers having different views and belongingness on this issue. Even follow up review five years after the introduction of revised guidelines has failed to resolve the controversies and it deems un resolvable in near future. In such circumstances, every country needs to have own guideline for uniform medical teaching and practice.